Quantitative laser diagnostics on trimethylindium pyrolysis and photolysis for functional nanoparticle growth. (1st May 2022) - Samuelsson, Per; Magnusson, Martin H; Deppert, Knut; Aldén, Marcus; Li, Zhongshan
Abstract: We report on an optical investigation of the pyrolysis and photolysis of trimethylindium (TMIn) as a typical metalorganic precursor for functional nanowire growth, aiming at an in-depth understanding of the governing chemistry and optimization of aerosol-based (aerotaxy) and epitaxial growth processes. A flow reactor with special consideration given to optical access was built to provide the chemical environment for in situ optical measurements on the pyrolysis and photolysis of TMIn. By probing a resonant transition of the indium atom, high-resolution laser absorption and laser-induced fluorescence spectroscopy were applied to obtain the atomic indium concentration at different chosen conditions in a spatially and temporally resolved manner. The results indicate that quantitative measurements of indium atoms under growth conditions are feasible. A 213 nm pulsed laser was employed to induce photolytic dissociation of TMIn vapor under chosen conditions. The photolytic dissociation of TMIn vapor with an ultraviolet laser turns out to be a promising method in generating substantial chemical effects, indicated by the generation of visible clouds of indium particles, and high concentrations of indium atoms far beyond the pyrolytically generated amount.